A multicentre prospective randomised controlled comparative parallel study of dehydrated human umbilical cord (EpiCord) allograft for the treatment of diabetic foot ulcers - Tettelbach, William; Cazzell, Shawn; Sigal, Felix; Caporusso, Joseph M.; Agnew, Patrick S.; Hanft, Jason; Dove, Cyaandi (International wound journal, 2019)
The aim of this study was to determine the safety and effectiveness of dehydrated human umbilical cord allograft (EpiCord) compared with alginate wound dressings for the treatment of chronic, non‐healing diabetic foot ulcers (DFU). A multicentre, randomised, controlled, clinical trial was conducted at 11 centres in the United States. Individuals with a confirmed diagnosis of Type 1 or Type 2 diabetes presenting with a 1 to 15 cm2 ulcer located below the ankle that had been persisting for at least 30 days were eligible for the 14‐day study run‐in phase. After 14 days of weekly debridement, moist wound therapy, and off‐loading, those with ≤30% wound area reduction post‐debridement (n = 155) were randomised in a 2:1 ratio to receive a weekly application of EpiCord (n = 101) or standardised therapy with alginate wound dressing, non‐adherent silicone dressing, absorbent non‐adhesive hydropolymer secondary dressing, and gauze bandage roll (n = 54). All wounds continued to have appropriate off‐loading during the treatment phase of the study. Study visits were conducted for 12 weeks. At each weekly visit, the DFU was cleaned and debrided as necessary, with the wound photographed pre‐ and post‐debridement and measured before the application of treatment group‐specific dressings. A follow‐up visit was performed at week 16. The primary study end point was the percentage of complete closure of the study ulcer within 12 weeks, as assessed by Silhouette camera. Data for randomised subjects meeting study inclusion criteria were included in an intent‐to‐treat (ITT) analysis. Additional analysis was conducted on a group of subjects (n = 134) who completed the study per protocol (PP) (EpiCord, n = 86, alginate, n = 48) and for those subjects receiving adequate debridement (EpiCord, n = 67, alginate, n = 40). ITT analysis showed that DFUs treated with EpiCord were more likely to heal within 12 weeks than those receiving alginate dressings, 71 of 101 (70%) vs 26 of 54 (48%) for EpiCord and alginate dressings, respectively, P = 0.0089. Healing rates at 12 weeks for subjects treated PP were 70 of 86 (81%) for EpiCord‐treated and 26 of 48 (54%) for alginate‐treated DFUs, P = 0.0013. For those DFUs that received adequate debridement (n = 107, ITT population), 64 of 67 (96%) of the EpiCord‐treated ulcers healed completely within 12 weeks, compared with 26 of 40 (65%) of adequately debrided alginate‐treated ulcers, P < 0.0001. Seventy‐five subjects experienced at least one adverse event, with a total of 160 adverse events recorded. There were no adverse events related to either EpiCord or alginate dressings. These results demonstrate the safety and efficacy of EpiCord as a treatment for non‐healing DFUs.